Differential Requirement of Beclin 1 for Regulating the Balance of Naïve and Activated CD4+ T Cells - Xia, Rui; Yang, Min; Fu, Xiaorui; Du, Wenwen; Gao, Xin; Li, Gang; Ranganathan, Sarangarajan; Zhang, Xueguang; Jiang, Jingting; Lu, Binfeng (Frontiers in Cell and Developmental Biology, 2020)
Autophagy is highly regulated and plays a multitude of roles during T cell-mediated immune responses. It has been shown that autophagy deficiency in T cells results in a decrease in total T cells, including naïve T cells in young mice, but the mechanism is still not understood. Here, similar to what happened in young mice, we showed that T cell-specific deletion of Beclin 1/Atg6 (Becn1 -/-) resulted in decreases in the percentages of CD4+, CD8+, and regulatory T cells in adult mice. In addition, we found that the effector to naïve T cell ratio was increased in older mice. Also, as mice grew older, Becn1 -/- mice progressively lost weight and developed severe colitis. Analysis of inflamed tissues demonstrated increases in the portion and cytokine production of effector T cells. In contrast, the TCR-transgenic Becn1 -/- mice had similar numbers of naïve T cells compared to WT controls. Similar to bulk T cells, the TCR-transgenic Becn1 -/- T cells generated much lower numbers of effector T cells compared to WT controls after activation in vitro. These data suggest that autophagy is not required for maintaining the naïve T cell but required for the generation of effector T cells in vivo.